2021
DOI: 10.1002/aic.17133
|View full text |Cite
|
Sign up to set email alerts
|

Cation–dipole interaction that creates ordered ion channels in an anion exchange membrane for fastOHconduction

Abstract: Precise control over polyelectrolyte architecture, engineered for self-assembly of ion-conducting channels, is of fundamental and technological importance to many fields, for example, fuel cells and redox flow batteries and electrodialysis. Building on recent advances with the supramolecular chemistry, we introduce inter/intramolecular cation-dipole interactions between pendent quaternary ammoniums cations and polar polyethylene glycol grafts in an anion-exchange membrane (AEM). Such interactions lead to desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 72 publications
(112 reference statements)
1
39
0
Order By: Relevance
“…Generally, the AEMs are fabricated by amorphous polymers, with so many structural disorders hindering efficient ion transport, therefore showing low conductivity. Precise control over AEM structures to form the desired microphase separation morphology is believed to accelerate ion transport across the membrane through the continuous ionic channels. Over the past decades, AEMs featuring the block, clustered, , side-chain, or graft/comb-shaped structure , have been successfully designed to construct the aforementioned ionic channels.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the AEMs are fabricated by amorphous polymers, with so many structural disorders hindering efficient ion transport, therefore showing low conductivity. Precise control over AEM structures to form the desired microphase separation morphology is believed to accelerate ion transport across the membrane through the continuous ionic channels. Over the past decades, AEMs featuring the block, clustered, , side-chain, or graft/comb-shaped structure , have been successfully designed to construct the aforementioned ionic channels.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers usually enhance ion conductivity by increasing the ion-exchange capacity (IEC). ,, However, high IEC often leads to excessive water uptake, which easily deteriorates the mechanical stabilities of membranes. , The difference in polarity of the hydrophilic/hydrophobic regions in membranes can induce ion aggregation and promote the formation of ion transport channels, which improves the ion conductivity of AEMs . Furthermore, introducing spontaneous intermolecular interactions, such as a hydrogen bond, dipolar interactions, and a π–π stacking interaction, can further accelerate the self-aggregation of hydrophilic cations in AEMs. , Xu et.al reported a PPO-based AEM grafted with a PEG homopolymer, which can form an abundant cation–dipole interaction network. The resulting membrane showed that cation–dipole interactions (between quaternary ammonium cations and PEG moieties) provide an additional driving force for hydrophilic QA self-aggregation, promoting the formation of a well-defined microphase separation.…”
Section: Introductionmentioning
confidence: 99%
“…However, low ionic conductivity and poor stability, especially poor chemical stability, have always been the major problems that lie in the way of AEM development. To address the above problems, several strategies have been proposed, including the design of stable cation exchange groups, alkaline-resistant polymer backbone (e.g., without the benzyl- ether group), microphase separation, semi-interpenetrating polymer network (IPN)/IPN structure, cross-linking, blending, and hybridization. Encouraging results have been achieved, for instance, a cross-linked poly­(norbornene) PTFE-supported membrane showed a high conductivity of 198 mS cm –1 @80 °C, with no significant decay after 1000 h under 1 mol L –1 KOH at 80 °C . The poly­(aryl piperidinium) membrane was prepared by inducing the strong basic piperidinium cationic group onto the rigid hydrophobic aryl backbone without the ether bond, which showed conductivity of 170 mS cm –1 @80 °C and durability of over 2000 h …”
Section: Introductionmentioning
confidence: 99%